Massive Fatal Pulmonary Embolism While on Therapeutic Heparin Drip - Said Hajouli MD (SAGE Publishing, 2020)
Venous thromboembolism (VTE) includes deep venous thrombosis (DVT) and pulmonary embolism (PE). In this article, we present a case of a patient with an acute DVT who was treated with a therapeutic heparin drip, then developed syncope while in the hospital and found to have massive bilateral PEs. This case aims to arouse the medical staff's awareness of the VTE diagnosis even if the patient is fully anticoagulated. We review the indications for DVT hospitalization, heparin infusion monitoring, risk factors for developing PE from DVT, mechanisms of developing PE from DVT while on therapeutic anticoagulation, and signs and treatment of massive PE.